2002
DOI: 10.1002/cjoc.20020201209
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Model for Regulation of the Allosteric Enzyme Activity

Abstract: Keywords ity , h-i c effect, activator molecule, repressive molecule d&c enzyme, coopedvity and anticwperetiv-*

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…20,21 Employing nanoparticles as building blocks offers a powerful tool to succeed in fabrication of desired 1-3 D (dimensional) nanoarchitectures of Co 3 O 4 . 9,22,23 Its nanostructures with a great variety of morphologies, such as nanocubes, 24,25 nanorods, 7,26 nanowires, 27,28 nanotubes, 10,29 nanobelts, 30,31 nanospheres, 14,32 nanosheets, 33,34 nanomeshs, 35 nanooctahedra, 36 and nanocapsules, 37 etc., have been fabricated. Further investigations discovered that there is a close correlation between shape/morphology and performances of Co 3 O 4 nanocrystals in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Employing nanoparticles as building blocks offers a powerful tool to succeed in fabrication of desired 1-3 D (dimensional) nanoarchitectures of Co 3 O 4 . 9,22,23 Its nanostructures with a great variety of morphologies, such as nanocubes, 24,25 nanorods, 7,26 nanowires, 27,28 nanotubes, 10,29 nanobelts, 30,31 nanospheres, 14,32 nanosheets, 33,34 nanomeshs, 35 nanooctahedra, 36 and nanocapsules, 37 etc., have been fabricated. Further investigations discovered that there is a close correlation between shape/morphology and performances of Co 3 O 4 nanocrystals in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…[3,[14][15][16][17] It has been reported that significant conformational variations could be identified in a variety of protein-ligand interactions and can be generally attributed as allosteric transitions of proteins. [18][19][20][21][22][23][24] The mechanisms of corresponding conformational and micro-environmental changes could provide new venues for pharmacological studies of drug ligands. [14,25] Non-the HSA molecules are preferred for developing strategies of affinity-controlled release.…”
Section: Introductionmentioning
confidence: 99%